Growing beyond the D.F.O - Das, Siddhanta (Indian Forester, 1997)
The paper discusses the management of forest administration at three levels, viz. (1) Policy making, (2) Supervisory level, (3) Executive level and role of the 'DFO' for the most optimal and efficient management of forest resources.